Adeno-associated virus (AAV) site-specific recombination does not require a Rep-dependent origin of replication within the AAV terminal repeat - Young, Samuel M. (The National Academy of Sciences, 2001)
Adeno-associated virus (AAV) is the only known eukaryotic virus capable of targeted integration in human cells. An AAV Rep binding element (RBE) and terminal resolution site (trs) identical to the viral terminal repeats required for AAV DNA replication are located on chromosome (ch) 19. Both ch-19 RBE and trs elements have been shown to be essential for viral targeting to this locus. To characterize the role of the AAV inverted terminal repeat (ITR) cis-acting sequences in targeted integration an AAV trs mutant incapable of supporting viral replication was tested. Wild-type and mutant substrates were assayed for targeted integration after cotransfection in the presence or absence of Rep. Our results demonstrated that, in the presence of Rep78, both ITR substrates targeted to ch-19 with similar frequency. Molecular characterization of the mutant ITR integrants confirmed the presence of the trs mutation in the majority of samples tested. Complementation analysis confirmed that the mutant targeted viral genomes were unable to rescue and replicate. In addition, Rep78 induced extensive rearrangement and amplification of ch-19 sequences independent of wild-type or mutant targeting substrate. These studies demonstrate that Rep-dependent nicking of the viral cis-acting trs sequence is not a prerequisite for site-specific recombination and suggests AAV targeting is mediated by Rep78/68-dependent replication from the ch-19 origin of replication (ori). These studies have significant impact toward the understanding of AAV site-specific recombination and the development of targeting vectors.